Sequência didática utilizando laboratório com materiais de baixo custo em calorimetria, óptica e eletromagnetismo. - Souza, Ronaldo Zacarias de (2020)
This work proposes a didactic sequence with experimental practices using recycled and low-cost materials for high school students at the Helenita Lopes Gurgel Valente High School, located in the city of Fortim - CE, envisioning a potentially meaningful learning. Due to the reality of classrooms in public schools, unfortunately the use of experimental activities hardly happens, making the subject of physics only theoretical and with exhaustive mathematical language. One reason is the lack of laboratories, or when they exist, there are no materials to carry out the experiments. The experimental classes directly and playfully contribute to the verification of concepts presented in the theoretical classes, in addition to the construction of scientific thinking that arouses interest in physics in the school environment, as well as the development of experimental skills by students. The didactic sequence presents three experiments for the 2nd series, on the themes: thermal expansion, calorimetry and optics; and three experiments in the 3rd series: electrostatics, electrodynamics and electromagnetism. Lev Semyonovitch Vygotsky's theories of learning were used, which is based on social interaction between individuals, and on David Ausubel's theory of meaningful learning. Each practice took place in six hours / classes, one practice per bimonth, starting from the 2nd bimonth. The methodology used in each practice was: surveys of previous knowledge; relationship between practice and daily life, without teacher intervention; theoretical foundation; conducting the experiment and verifying the learning of the content discussed. During the application of the product we noticed that there was a significant growth in the presence of students and in the participation of classes and that the experiments related to daily life allow a better construction of knowledge for the student.